BOOK REVIEW. FUNCTION AND MEANING OF NGUSABA GEDE LANANG KAPAT RITUALS IN TRUNYAN VILLAGE - Nopita Trihastutie (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
This book is the result of a historical, sociological and cultural study on the Ngusaba Gede Lanang Kapat ritual promoted by the Preservation Office of Balinese Cultural Values. In his forwards, the chairman states that this book is an effort to save the endangered cultural work and to load the local content in the areas where this work culture is alive and thriving (p. xi). Conducted in Trunyan, a village in which the daily life of the people governed by customary law, the result of the study presented in this book, as noted in the authors’ remarks (p. xii), provides a comprehensive understanding of Trunyan local genius as expressed in their customary rules, arts, rituals, and folklores.